Too-Systemic-to-Fail: What Option Markets Imply about Sector-Wide Government Guarantees - Kelly, Bryan; Lustig, Hanno; Van Nieuwerburgh, Stijn (American Economic Review, 2016)
We examine the pricing of financial crash insurance during the 2007–2009 financial crisis in US option markets, and we show that a large amount of aggregate tail risk is missing from the cost of financial sector crash insurance during the crisis. The difference in costs between out-of-the-money put options for individual banks and puts on the financial sector index increases four-fold from its precrisis 2003–2007 level. We provide evidence that a collective government guarantee for the financial sector lowers index put prices far more than those of individual banks and explains the increase in the basket-index put spread. (JEL E44, G01, G13, G21, G28, H81)